Why the fuss continuing breastfeeding - Abd Alla Yousseff, Nivin Essameldin (2015)
The statistic have shown that the breastfeeding initiation rate in Malaysia is high (90%) but most mother did not continue to breastfeed their child beyond the age of 4 months as recommended by who. One of the reasons that these mothers stopped breastfeeding is because they lack support from people around them specially their employers.